Analysis of the Influence of the Use of Fintech Services on Investment Decisions of Millennial Communities in the Digital Age - Ratih Astiakurnia Putri; Andi Ihsan Triputrajaya (Journal of Social Science, 2024)
The development of digital economy in Indonesia is growing rapidly along with the increasing use of internet and technology in various sectors. Fintech services are one of the main drivers of this development, especially in increasing financial inclusion. This study aims to explore the impact of fintech services on investment decisions among millennials. This study uses quantitative method with survey as the data collection technique, involving respondents who are active users of fintech platforms. The data collected was analysed using linear regression. The results of the analysis show that ease of access, low cost, transparency and time flexibility significantly influence their investment decisions. In addition, the study identified the importance of financial education in improving users' literacy and confidence in investing. The findings emphasise the important role of fintech in encouraging millennial participation in financial markets, as well as the need for appropriate regulation to protect consumers and support the industry's sustainable growth